Seatbelt Design Awareness and Factors for Intercity Express Bus in Peninsular Malaysia - Ibrahim, Siti Zubaidah; Majid, Ahmad Zuhairi Abdul (Science & Engineering Research Support Society, 2020)
Road collisions and injuries are major challenges encountered in developing countries including Malaysia. According to statistics stated by the Royal Malaysian Police (RMP) and reviews from the Malaysian Institute of Road Safety Research (MIROS), more than 6,000 deaths per year were reported due to road collisions. This includes road accidents involving intercity express buses (IEB) which started in 2003 and keeps increasing from 2007 until 2017. In fact, accidents involving IEB and town buses were rated as the highest. Therefore, this study was performed in order to reveal safety factors for safety awareness on intercity express busses. Besides, this paper also provides a study on seatbelt design awareness that focuses on the passengers and enforcement authorities responded by the southern, center, east coast and northern region of intercity express bus passengers. Simultaneously, this study aims to improve the percentage of seatbelt usage by passengers. Evidence found in this study shows that the main cause of seatbelt design awareness is because of passengers themselves have great safety awareness and also enforcement by the authority. Hence, seatbelt design awareness for passengers' safety should be implemented to improve the percentage of seatbelt usage as well as the enforcement by every intercity bus provider